Ragam Flora Fauna Di Kawasan Cagar Budaya Nasional Muarajambi Berdasarkan Data Arkeologi - Asyhadi Mufsi Sadzali; Wenda Emafri; Altahira Wadhah; Rosaria Nabila Huda; Yenci Alione Sihite; M. Alif Zulkifli (Proceeding International Conference on Malay Identity, 2022)
Abstract: The Muarajambi National Heritage Reserve is spread over 2 districts; and 8 Villages in Muarajambi Regency, Jambi Province with an area of ??3,981 Ha. The concentration of structures that have been excavated and restored is 12 sites, mostly located in Muarajambi Village, which is administratively within the Marosebo sub-district, Muarajambi district. The diversity of flora and fauna is reflected in various archaeological findings in the Muarajambi National Cultural Heritage Area, including the makaras in the Kedaton, Gumpung and Koto Mahligai temples. Not only limited to makara, but also ceramics with elements of flora and fauna, as well as bricks with pictures found in several temples. The existence of these artifact findings was tried to be analyzed for their suitability with the existence of biodiversity in the Muarajambi KCBN in the past 7th to 13th centuries AD. This is a research question that will be answered with qualitative research methods of archaeological approach with the stages of data collection, data identification, data analysis and interpretation. data. The results of the study illustrate that the inspiration from archaeological findings with the theme of biodiversity at the Muarajambi KCBN was based on descriptions of the flora and fauna that lived at that time, but some of them were mythological animals that were unreal and mystical in nature to fulfill religious needs. Keywords: Biodiversity, past, Muarajambi KCBN, artefacts.